Desenho e Escala - Ana Rita Vale da Silva (2016)
This work proposes to study some of the modern concepts, that emerged during the first decades of the twentieth century, along with the Modern Architecture. We aim to understand the ruptures with the past and enhance the new concepts of the Modern Movement, through the study of the artistic movements, the mentality of society, the reality of the time and the needs of the population. This thesis analyses the modern ideals, that were originally applied to the minimum housing, by unfolding them in a different reality and context. We intend to explore these concepts, in particular the notion of minimum, in order to find different relationships and adaptations of the same ideals, within the context of the bourgeois housing. For that, we looked into two case studies, the Villa Tugendhat (1928-1930), Mies van der Rohe (1886-1969), and the Maison de Verre (1928-1932), Pierre Chareau (1883-1932). The development of this work focuses on the attention given to the various stages of the architectural design, resulted from the recovering by the architects of the whole house's design and project. Since the houses are projected from the whole to the particular, we studied the different scales of domestic design, through the application of the themes and modern ideals in the living spaces and furniture. By having the human scale as a base, we propose to understand the relationships between the whole and the parts, being the whole formed by the inhabitant, the furniture and the housing. The present study also focuses in understanding the different stages of the architectural project and design.